SrCO3 Assisted Synthesis of Disk-Like Micron-Sized Monocrystalline LiNi0.5Co0.2Mn0.3O2 with Preferred (104) Plane and Its Enhanced Cycle Performance. Issue 14 (19th October 2020) - Hu, Guorong; Li, Luyu; Lu, Yan; Cao, Yanbing; Peng, Zhongdong; Xue, Zhichen; Zhang, Yinjia; Fan, Ju; Du, Ke
Abstract : Disk-like micron-sized monocrystalline LiNi0.5 Co0.2 Mn0.3 O2 is synthesized by the co-precipitation method accompanied with calcination assisted by strontian carbonate without washing process or other complicated treatment. Powder X-ray diffraction, scanning electron microscopy, and transmission electron microscopy are used to characterize the obtained samples. Characterizations reveal that the addition of SrCO3 help to form monocrystalline LiNi0.5 Co0.2 Mn0.3 O2 with preferred (104) plane, and the particle is disk-like and in micrometer size. Electrochemical test results indicate that the LiNi0.5 Co0.2 Mn0.3 O2 exhibits significantly improved capacity retentions of 95.6% and 89.3% after 100 cycles at 1C, for the voltage ranges of 2.8−4.3 V and 2.8−4.5 V, respectively. The excellent cycle performance of the LiNi0.5 Co0.2 Mn0.3 O2 is ascribed to the unique monocrystalline morphology, high stability of (104) plane and reduced irreversible phase transition.